Marketing of Crop Residues in Niamey city: Socio-organizational Aspects - Lawal, A.A. Maman; Chaibou, M.; Hamadou, I.; Gouro, A.S. (International Journal of Environment, Agriculture and Biotechnology, 2019)
A sample of 93 stakeholders was surveyed and monitored to analyze the socio-economic and organizational aspects of the marketing of crop residues used in animal feed in the city of Niamey. It emerges from this study that almost all the actors are male. More than 45% of actors are between 40 and 60 years old. The Hausa ethnic group is the majority of wholesalers / semi-wholesalers (54.5%). Those of the Zarma ethnic group are more numerous at the level of sellers / resellers (92.7%), while those of the Fulani ethnic group represent the majority of street vendors (57.9%). Inheritance and profitability were the main reasons that led to the activity of wholesalers / semi-wholesalers (30.3% and 24.2%) and street vendors (26.3% and 31%). 6%). Among sellers / resellers, it is rather survival (24.4%), passion (22%) and constraint (22%). Most wholesalers / semi-wholesalers (60.6%) and sellers / resellers (68.3%) are supplied and delivered locally at their own point of sale. cash settlement is the most common (79% for wholesalers / semi-wholesalers, 61% for sellers / resellers and 74% for street vendors). The daily gross margin of a wholesaler / semi-wholesaler of crop residues is 14753.03 ± 25724.24FCFA. It is higher than that of street vendors (6946.05 ± 2204.23FCFA), which is also higher than that of sellers/resellers (5855.54 ± 5065.49FCFA). In short, the marketing of crop residues is a very profitable activity for the actors, especially in the cold dry season. However, the recurrent displacements of actors for lack of fixed places and the harassment of the collection agents from the municipalities represent a brake on the development of this activity. It is therefore imperative to regulate their implementation while facilitating administrative procedures leading to the granting of authorization for installation.